Guidelines to using evidence from research to support policymaking. ([World Intellectual Property Organization (WIPO)], 2019)
This Guide elaborates on the best practices in conducting empirical studies in the intellectual property (IP) field. In so doing, it seeks to improve the credibility of studies, enhance transparency about what conclusions can and cannot be drawn from such studies, and encourage responsible use of studies by IP stakeholders.